Assessment of degradation potential of Pseudomonas species in bioremediating soils contaminated with petroleum hydrocarbons. Issue 2 (26th June 2021) - Baig, Zenab Tariq; Abbasi, Sikandar Ali; Memon, Abdul Ghaffar; Naz, Alia; Soomro, Abdul Fatah
Abstract: BACKGROUND: The bioremediation versatility of soil indigenous microbial community for the degradation of oil contaminated soils has been evidenced previously. In this study, three dominant bacterial strains, Pseudomonas putida (P. putida) and two Pseudomonas aeruginosa (P. aeruginosa ) (accession numbers ATCC‐27853, BAA‐427, and ATCC‐49128), were isolated from three different oil‐contaminated sites to evaluate their bioremediation potential. Degradation potential was determined against two compounds, naphthalene and pyrene, from polycyclic aromatic hydrocarbons (PAHs) in batch experiment. RESULTS: The bacterial strains were effective in degrading naphthalene and pyrene. Further, the degradation potential of these compounds was correlated with total organic carbon (TOC). Among the bacterial strains, P. putida (accession number ATCC‐27853) effectively degraded naphthalene and pyrene by 92% and 83%, respectively. The other bacterial strain, P. aeruginosa (ATCC‐27853), equally degraded the naphthalene (83.6%) but differed considerably for pyrene, with the lowest removal efficiency of 24.2% at 3 ppm. Growth profiles of the proposed bacterial strains, P. putida (accession number ATCC‐27853), P. aeruginosa (accession number BAA‐427), and P. aeruginosa, ATCC‐49128), revalidated through colony‐forming unit (CFU·mL −1 ). P. putida showed the highest cell count 5.06 × 10 8 (CFU·mL −1 ) for naphthalene. CONCLUSION: This study highlights that isolated Pseudomonas strains showed the highest degrading activity for naphthalene and pyrene‐degrading without the addition of any chemical or co‐substrate within a short interval. Overall, findings indicate that inoculation of the bacterial strains belonging to Pseudomonas species can stimulate low and high weight PAH compounds degradation and maintain the bacterial biomass, thus accelerating the dissipation of soil PAHs. It further provides evidence for perspectives on the potential of bacterial community assembly of PAH‐contaminated soils. © 2021 Society of Chemical Industry (SCI).